Running Wild: Environmental Attitudes of Long-Distance Runners in the Icelandic Highlands - Rannveig Ólafsdóttir; Anna Dóra Sæþórsdóttir; Edita Tverijonaite (Mountain Research and Development, 2021)
An increasing number of sports events are taking place in wilderness and mountain areas. The Laugavegur Ultra Marathon (LUM) is one such event. It follows the 55-km (34.2-mile) route of the Laugavegur trail in the southern Icelandic highlands. The trail has been selected as one of the world's most scenic long-distance hiking trails by many of the world's leading travel media. This paper focuses on LUM runners' attitudes toward environmental issues to identify their values as a group and to examine whether there are different attitudes between Icelandic and international runners. An online survey was distributed to all participants finishing the race in 2018, a total of 553 runners; the response rate was 45.2%. The results reveal that most runners participating in LUM were running for their own personal goals and challenges, using the trail's wilderness setting as a driver to reach their target. As a group, the runners had relatively ecocentric orientations. With regard to environmental values, however, there was a large difference between Icelandic and international runners. The Icelandic runners significantly favored anthropocentric orientations, preferring more infrastructure and services along the route, compared with international runners, who preferred the wild character of the route. When it comes to planning sports events in natural settings, such as mountain marathons in wilderness areas, it is important to raise the environmental awareness of both users and event organizers. Moreover, to sustain the wilderness character of the trail, it is beneficial to attract more runners who have an ecocentric view.